Ministerial Decree 24/2017 Concerning the Strategic Agricultural Goods = قرار وزاري رقم 24 لسنة 2017 بشأن السلع الزراعية الإستراتيجية / Prime Minister - Egypt. Prime Minister (2025)
Decree no. 24 of the year 2017 concerning the strategic agriculture goods – قرار وزاى رقم 24 لسنة 2017 بشأن السلع الزراعية الإستراتيجية